Vascular occlusion strength training: An alternative to high resistance strength training - Brandner, C. R. (Journal of Australian Strength and Conditioning, 2012)
Traditional high-load resistance strength training induces hypertrophy of skeletal muscle and increases maximal strength, whilst low-load resistance training protocols typically induces local muscular endurance without any significant increase in hypertrophy or strength. However, recent evidence suggests that when low-load resistance strength training protocols are combined with vascular occlusion, the muscle hypertrophy and strength response is similar to or even greater than traditional high-load resistance exercise. Vascular occlusion is a technique that involves reducing blood flow to muscle during exercise training via an inflated compressive cuff or tourniquet. While the mechanisms that result in muscular adaptations are relatively unknown, acute responses to training such as an increase in motor unit recruitment, in particular the preferential recruitment of type II fibres, and the increase in circulating human growth hormone, have been well characterised. This type of training would be suitable to a host of common pathologies where heavy resistance strength training is not possible such as the elderly, patients in early rehabilitation following injury, or where muscle atrophy and weakness occur due to the effects of inactivity or disease. For athletes, rapid increases in strength while training at such low intensities may be of interest, however, research in this population is limited.